Kekayaan Flora di Kecamatan Mangkubumi Yang Potensial Dapat Dimanfaatkan Sebagai Pestisida Nabati Ramah Lingkungan - Esta Rendra RS (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2024)
This research aims to know the types of floras and their distribution in Mangkubumi District area it has potential to be enviromentally friendly botanical pesticides. This reserch carried out in Mangkubumi District, Tasikmalaya City for three months from Agustus to Oktober 2023. The methode used in this research is literature study. Two data collected in this research namely primary data and secondary data. Primary data collected by field observation to find the types of plant in Mangkubumi District its potential as botanical pesticides, while secondary data was obtained by conducting literature studies. Based on tne results of field observations and literature studies, 8 types of plant were found has potential as botanical pesticides to treat various plant diseases such as aphids, whitefly, fruit flies, planthopper pets, caterpillars, etc